O empoderamento das identidades de gênero feministas pela cibercena/educação infantil crítica no DEI/CEPAE/UFG - Lyra, Yasmin Gonçalves e (2023)
The research in question has as impellent the study about the critical Early Childhood Cyberscene/Education in favor of the empowerment of feminist gender identities, with children aged 4 to 6 years from the Department of Early Childhood Education of the Center for Teaching and Applied Research to Education at the Federal University of Goiás – DEI/CEPAE/UFG. As a Cyberactress/Educator at that institution, the perception of sexist gender identity stereotypes is raised, present in the metacenic expressions of children aged 4 to 5 years old through the child play that composes the aesthetics of everyday school life, stereotypes that may be reinforcing iniquitous power relations in the binary representations of masculine and feminine that make up the ontological formation of children. The metacenic expressions of gender identity stereotypes are phenomenally analyzed from the visualities of the scene through iconographic and audiovisual records, interviews with the children's families and reports of pedagogical activities written by DEI/CEPAE/UFG teachers. Thus, a Cyberscenic/Educational intervention was developed for children from 4 to 6 years of age at DEI/CEPAE/UFG, by the Cybertheater Forum with Animated Forms, based on the Triangular Approach developed by Professor Ana Mae Barbosa, on the Digital Triangular System systematized by Professor Fernanda Cunha , and on Aesthetics of the Oppressed by Augusto Boal, for the promotion of aesthetic-scenic resignifications regarding the cognitive perception of personal identity through the concept of Artist Cyberlife. Feminism is understood in this study as a political movement in favor of gender equality, against institutionalized sexism that establishes unequal power relations through oppression from an early age.